Can non-linear real shocks explain the persistence of PPP exchange rate disequilibria? - Tuomas A. Peltonen; Adina Popescu; Michael Sager (European Central Bank (ECB), 2009)
A core stylized fact of the empirical exchange rate literature is that half-life deviations of equilibrium real exchange rates from levels implied by Purchasing Power Parity (PPP) are very persistent. Empirical efforts to explain this persistence typically proceed along two distinct paths, resorting either to the presence of real shocks such as productivity differentials that drive equilibrium exchange rates away from levels implied by PPP, or the presence of non-linearities in the adjustment process around PPP. By contrast, we combine these two explanations in the context of an innovative panel estimation methodology. We conclude that both explanations are relevant to the behavior of exchange rates and that resulting half-lives are much shorter than estimated using linear PPP and more consistent with the observed volatility of nominal and real exchange rates.
Keywords: F31; C23; 330; Balassa-Samuelson; EPSTAR; exchange rate; PPP; productivity; Kaufkraftparität; Wechselkurs; Balassa-Samuelson-Effekt; Produktivität; OECD-Staaten